A randomised placebo controlled study to assess the effects of cholinergic treatment on muscarinic receptors in Alzheimer's disease. Issue 11 (14th November 2003) - Kemp, P M; Holmes, C; Hoffmann, S; Wilkinson, S; Zivanovic, M; Thom, J; Bolt, L; Fleming, J; Wilkinson, D G
Abstract : Objective: To determine the effects of cholinergic treatment on the muscarinic receptor in patients with Alzheimer's disease. Methods: 12 patients with mild to moderate Alzheimer's disease and six controls were studied. The patients underwent ADAS-COG psychometric assessment and SPECT brain imaging with 123 I quinuclidinyl benzilate (QNB), to demonstrate the postsynaptic muscarinic M1 receptor, before being randomised in a double blind study to receive either an acetylcholinesterase inhibitor (donepezil) or placebo for four months. Following this, the ADAS-COG and the 123 I-QNB receptor scan were repeated. The controls were imaged on one occasion only. All image analyses were undertaken using SPM99. Results: 123 I-QNB imaging showed a significant relation between baseline psychometric impairment and deficits on scanning. Both placebo and actively treated groups had reductions in 123 I-QNB uptake. Greater reductions in receptor binding were demonstrated in the placebo group than in those receiving active treatment. Intraindividual reproducibility of the 123 I-QNB imaging technique appeared highly robust. Conclusions: The results suggest that 123 I-QNB uptake is better preserved in Alzheimer's disease patients on cholinergic treatment than on placebo. Cholinergic treatment may play a neuroprotective role. Sequential 123 I-QNB imaging seems to be a powerful tool in monitoring the response of these receptors to disease modifying treatments.